Everything you need to know about frogs and other slippery creatures - Love, Carrie (London ; New York : DK Pub., 2011)
Photographs and text provide an overview of reptiles and amphibians, with information on their habitat, behavior, physical characteristics, diet, and breeding habits.
Includes index.
5.0
3-6.
3-6
Keywords: Amphibians -- Juvenile literature; Frogs -- Juvenile literature; Reptiles -- Juvenile literature; Amphibians; Frogs; Reptiles; Amphibians; Frogs; Reptiles